Can Drug Effects Help Elucidate the Pathogenesis of SLE? - Fang, Celia J.; Hahn, Bevra H.; Furst, Daniel E. (Current Rheumatology Reviews, 2006)
Systemic lupus erythematosus (SLE) is a complex disease involving many different immune mechanisms, whose pathogenesis is not fully understood. In the past therapeutic interventions have employed medications with multiple immunological targets, making their use as probes of disease mechanisms difficult. For example, prednisone and cyclophosphamide, the most widely used therapies for severe disease until recently, affect such a broad array of immune mechanisms that they do not help identify the most important immunological SLE pathways. While examining the efficacy and toxicity of some of the new targeted therapies, this review will address what specific agents tell us about the pathogenesis of SLE. These include anti-CD20 and BlyS antibody, B and T cell co-stimulatory blockade such as anti- CD40L antibody and CTLA4Ig, therapies aimed at decreasing dsDNA specifically, as well as cytokine modulation with TNF alpha inhibitor, anti IL-10 ab, etc.
Keywords: Systemic lupus erythematosus